Design of an Ultrawideband Circularly Polarized Printed Crossed-Dipole Antenna Based on Genetic Algorithms for S-Band CubeSat Applications - Jorge Simon; Hugo Perez-Guerrero; Jorge Sosa-Pedroza; Fabiola Martínez-Zúñiga; Juvenal Villanueva-Maldonado; Jorge Flores-Troncoso; Marco Cardenas-Juarez (International Journal of Antennas and Propagation)
As in any satellite, onboard antennas for CubeSats are crucial to establish communication with ground stations or other satellites. According to its application, antennas must comply with standardized requirements related to size, bandwidth, operating frequency, polarization, and gain. This paper presents an ultrawideband circularly polarized two-layer crossed-dipole microstrip antenna for S-band CubeSat applications using genetic algorithms optimization tools included in the 3D electromagnetic simulation software Ansys HFSS. The antenna is constructed on a 10 × 10 cm Cuclad-250 substrate with a back copper flat plane, located at λ/4 at 2.25 GHz operating frequency. The backplane with the exact substrate dimensions improves gain and reduces inside satellite radiation. Measured bandwidth defined by S11 at a −10 dB was higher than 1835 MHz with S11 = −24.68 dB at the central frequency of 2.25 GHz, while measured VSWR at the same frequency was 1.124. At 2.25 GHz, the maximum measured gain and the minimum measured axial ratio in the broadside direction were found to be 6 dBi and 0.22 dB, respectively. There are antenna simulations and measurements, as long as its fabrication guarantees application requirements that make it ready for prespace testing.